Bipyridyl alkynyl-based polyphenylenes : tuning photoluminescence in metal-organic chromophores - Nolan, Deanne (Trinity College (Dublin, Ireland). School of Chemistry, 2011)
Chapter 1 introduces two series of novel polyphenylene molecules with inherent ligand functionality. These are prepared via a sequence of Sonogashira cross-coupling reactions and [2+4] Diels-Alder cycloadditions and are fully characterised by NMR spectroscopy and analytical methods. The first series are asymmetric oligophenylene-substituted bipyridines, in which the polyaryl pendant is systematically increased in size, from a single phenyl-acetylene to a dendritic penta-phenyl benzene. The second ligand series represents a family of acetylene-functionalised hexaphenylbenzene molecules, from a single acetylene substituent to ortho and para configured di-ethynyl units. The alkynyl substituent allows an extension of π-electron delocalisation.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.